1994
DOI: 10.1002/bjs.1800810926
|View full text |Cite
|
Sign up to set email alerts
|

Portal pyaemia following flexible sigmoidoscopy

Abstract: effects of culture conditions. Mol Cell Endocrinol 1983; 29: 35 Oosterum R, Verleun T, Zuyderwijk J, Lamberts SWJ. Growth hormone secretion by cultured rat anterior pituitary cells. Effects of culture conditions and dexamethasone. Endo-36 Ijzermans JNM, Marquet RL, Bouwman E, de Bruin RWF, van der Meide PH, Jeekel J. Successful treatment of colon cancer in 197-212. crinology 1983; 113: 735-41. British Journal of Surgery 1994,81,1337 Case report rats with recombinant interferon-gamma. Br J Cancer 1987; 5 6 795-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…Other infectious complications after colonoscopy and sigmoidoscopy include acute appendicitis (261-267), bacterial peritonitis (268,269), endocarditis (270)(271)(272)(273), and septicemia (274)(275)(276)(277). Two cases of Listeria monocytogenes meningitis and septicemia (278,279) and one case of Fournier's gangrene of the perineum have been described (280).…”
Section: Diagnostic and Therapeutic Upper Gastrointestinal Endoscopymentioning
confidence: 99%
“…Other infectious complications after colonoscopy and sigmoidoscopy include acute appendicitis (261-267), bacterial peritonitis (268,269), endocarditis (270)(271)(272)(273), and septicemia (274)(275)(276)(277). Two cases of Listeria monocytogenes meningitis and septicemia (278,279) and one case of Fournier's gangrene of the perineum have been described (280).…”
Section: Diagnostic and Therapeutic Upper Gastrointestinal Endoscopymentioning
confidence: 99%
“…Il était de 0 % et 1 % dans deux études [26,27]. Cependant, des cas d'endocardites et de septicémie étaient aussi associés à cet examen [28][29][30][31]. Concernant l'examen au rectoscope rigide, la bactériémie varie de 0 à 12 % selon les études [23].…”
Section: Points Essentielsunclassified
“…However, there are very few well-described cases where colonoscopy was I. G. Harnik ( ) The Mount Sinai Hospital, Department of Medicine e-mail: Ian.Harnik@mssm.edu thought to induce PLA [1,2], and as such liver abscess is generally not recognized as a complication of colonoscopy. Furthermore, Low et al [3] conducted a prospective assessment of the rate of bacteremia during lower endoscopy and found that there was no additional risk of bacteremia or clinical sepsis when polypectomy was performed during colonoscopy, versus surveillance colonoscopy.…”
mentioning
confidence: 99%